(untitled) (Journal of the College of Basic Education, 2022)
Postmodern theater formed a wide-ranging mole pole in the field of the current theater, as a result of the wide aesthetic development that characterized it, as it ranged in announcing the death of the familiar theatrical model and the emergence of the theater in the manifestation of its audiovisual dimensions, as the postmodern theater blows up any form of The forms of traditional construction that the traditional theater adhered to and instead established forms based on the plurality of meanings and their continuous openings to the aesthetic and artistic developments accompanying this openness, such as the massive information inflation; the continuous institutional openness; and the emergence of some critical and aesthetic theories such as (reception, interpretation and deconstruction) that overthrew the traditional discourse of the theater , which led to the openness of postmodern theatrical experiences to different aesthetics in form and content.